Factors Related to Kangaroo Mother Care Promotion for Preterm Infants - คันธวงศา, เกศินี; เอื้ออำนวย, มาลี; กลั่นกลิ่น, พิมพาภรณ์ (Nursing Journal CMU, 2017)
Kangaroo mother care for preterm infants is physically and psychologically beneficial for mothers and infants. This descriptive research aimed to study the promotion of kangaroo mother care of preterm infants in neonatal wards, and related factors in nursing practice. The samples consisted of: (1) 106 nurses who worked in neonatal wards, (2) 88 preterm infant mothers, and (3) 26 administrators or supervisors. Data were collected in 4 northern tertiary hospitals from October 2014 to January 2015. The research instruments used were (1) nursing practice of kangaroo mother care promotion for preterm infants questionnaire, and (2) the related factors of kangaroo mother care promotion questionnaire for each sample, which were developed by the researcher. Data were analyzed using descriptive statistics, Spearman correlation coefficient and Pearson correlation statistics. The findings revealed that: The average score for nursing practice of kangaroo mother care promotion for preterm infants was at a high (62.3 %) and a moderate level (36.8 %). Attitude, experiences, support from administrators / supervisors and workload responsibility of the nurses as perceived by nurses were significantly related to nursing practice of kangaroo mother care promotion (p < .01 and p <.05) but the nurses’ knowledge on kangaroo mother care was not statistically significantly related to nursing practice. Attitude, readiness of mothers, maternal opinion on preterm infant characteristics and maternal perception of support from medical staff as perceived by mothers were significantly related to nursing practice of kangaroo mother care promotion (p < .05), but the mothers’ knowledge on kangaroo mother care was not significantly related to nursing practice. Policies, nursing guidelines, instruments provided for kangaroo mother care promotion, appropriate workload allocation as perceived by administrators or supervisor were not significantly related to nursing practice on kangaroo mother care promotion. The results of this study can be used as basic information for nurses to enhance nursing practice of kangaroo mother care promotion for preterm infants.